2020
DOI: 10.3390/nano10010161
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green-Nexturastat A-PLGA Nanoparticles Combine Photothermal and Epigenetic Therapy for Melanoma

Abstract: In this study, we describe poly (lactic-co-glycolic) acid (PLGA)-based nanoparticles that combine photothermal therapy (PTT) with epigenetic therapy for melanoma. Specifically, we co-encapsulated indocyanine green (ICG), a PTT agent, and Nexturastat A (NextA), an epigenetic drug within PLGA nanoparticles (ICG-NextA-PLGA; INAPs). We hypothesized that combining PTT with epigenetic therapy elicits favorable cytotoxic and immunomodulatory responses that result in improved survival in melanoma-bearing mice. We util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…In this sense, biodegradable nanoparticles made of poly-D,L-lactic-co-glycolic acid (PLGA) may represent a suitable candidate to encapsulate DXI and deliver it slowly into the target tissue [4]. In addition, PLGA has been approved by the Food and Drug Administration and is one of the most successful biodegradable polymers [3][4][5][6]. Moreover, PEG has been widely used to reduce the clearance of PLGA nanoparticles (NPs) and it has been demonstrated that PEG coatings shield the surface from aggregation, opsonization, phagocytosis and prolong nanoparticles systemic circulation time [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, biodegradable nanoparticles made of poly-D,L-lactic-co-glycolic acid (PLGA) may represent a suitable candidate to encapsulate DXI and deliver it slowly into the target tissue [4]. In addition, PLGA has been approved by the Food and Drug Administration and is one of the most successful biodegradable polymers [3][4][5][6]. Moreover, PEG has been widely used to reduce the clearance of PLGA nanoparticles (NPs) and it has been demonstrated that PEG coatings shield the surface from aggregation, opsonization, phagocytosis and prolong nanoparticles systemic circulation time [5].…”
Section: Introductionmentioning
confidence: 99%
“…A critical consideration in optimizing nanoparticle-based PTT for combination with ICB is finding the appropriate thermal dose. We have demonstrated that immunogenic cell death occurs at a specific thermal window, depending on the cancer type [43,50,52]. Table 2 presents the temperatures attained during PTT in different tumor models reviewed here.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Various organic dyes such as cyanine-based dyes (e.g., indocyanine green (ICG)) including heptamethine cyanines (e.g., IR825, IR780, IR808, IR2) and phthalocyanines (e.g., metallo-naphthalocyanines), diketopyrrolopyrrole-based agents, croconaine-based dyes, porphyrinbased dyes, polymer-based dyes (e.g., polypyrrole) have been used for PTT either as free agents or within nanoparticles. These formulations have been used alone and in combination with chemotherapy, radiation therapy, immunotherapies or therapies targeting epigenetic modulation [50,125,126]. Here, we review the latest studies using the organic dyes ICG, polydopamine and IR820 as PTT agents in combination with ICB.…”
Section: Organic Dyesmentioning
confidence: 99%
“…Since PTT can induce antitumor immunity of the body, rational use and appropriate enhancement of body's antitumor immune process can be effective for tumor treatment. [ 59,62,63 ] In this case, Sun and coworkers [ 64 ] encapsulated a photothermal material, polydopamine (pDA), on the surface of attenuated Salmonella VNP20009 (pDA‐VNP) through the oxidative self‐polymerization in alkaline solution ( Figure ). Many kinds of immune cells participate in the therapy process.…”
Section: Solutions For the Defects In Photothermal Therapymentioning
confidence: 99%